Causas e reflexos do entrelaçamento das folhas primárias em plântulas de soja - Lazaretti, Norma Schlickmann (2020)
In order to investigate the causes and reflexes of the interlacing of primary leaves (seedlings) in soybean seedlings, this study was carried out. The water content of the substrate was tested, if there is a recurrence of interlaced leaves in the seeds produced in the subsequent harvest and the influence of different herbicides and among them the synthetic auxin, used in the desiccation of soybeans. Four experiments were conducted in the municipalities of Realeza and Cascavel, in the State of Paraná, using seeds from two soybean cultivars, the 55I57RSF IPRO (Zeus) and the 58I60RSF IPRO (Lança), produced in Rio Grande do Sul, Santa Catarina and in Paraná. Experiment I was carried out in a Seed Analysis Laboratory, with the two cultivars that previously presented the seedlings with and without the interlacing of the primary leaves, using different levels of water in the substrate to conduct the germination test. Experiment II was conducted in the field and the two cultivars were subsequently desiccated with the herbicides paraquat, paraquat dichloride and 2,4-D dimethylamine in the dosage recommended by the manufacturer and twice the dose, and the control. Experiment III was carried out in a pot, using the same treatments as in experiment I. Experiment IV was carried out in the field with seeds of cultivar 55I57RSF IPRO (Zeus) and seeds from other sources were also used, which also presented the interlaced primary leaves in the analyzes. In the conditions that were carried out, the experiments concluded that: the water content used to moisten the substrate for conducting the tests causes primary leaf interlaced in soybean seedlings. Seedlings with first leaf interlaced when they reach adulthood, show reduced productivity. In the seeds of the next generation there is no interlacing of the primary leaves. The use of 2,4-D dimethylamine in the dosage of 3.0 L ha-1 causes irreparable damage to the physiological potential of the seeds, causes the thickening of the hypocotyl and general atrophy of the root system and the aerial part of the seedlings, however it does not present relationship with the interlacing of primary leaves.